Hubungan Antara Penerapan Model Pembelajaran Problem Based Learning dengan Motivasi Belajar Mahasiswa Program Studi Ilmu Keperawatan - Fika Nur Indriasari (LPPM STIKES NOTOKUSUMO YOGYAKARTA, 2016)
Background: Problem Based Learning (PBL) is a method of student-centered learning. Students contributed a great deal in their own learning process that aims to develop the ability to solve the problem and to help students to acquire the necessary knowledge and skills. With the implementation of PBL method students are expected to be motivated. Objective: This study aims to determine the application of PBL learning model and learning motivation of students in STIKES Yogyakarta and learning model application PBL relationship with student learning motivation. Method: methods of research using cross sectional approach to sampling is determined by proportional stratified random sampling method. Data were analyzed using Pearson product moment correlation. Result: PBL learning model application in good enough category as many as 45 students (63.4%). Motivation of students in the high category as many as 42 students (59.2%). There is a significant correlation between the implementation of PBL learning method with learning motivation of students who demonstrated the value of p = 0.005 less than 0.01 (0.01> 0.005 ). Conclusion: The relationship between the application of PBL learning model with student learning motivation is significant.